Upaya peningkatan hasil belajar siswa dengan menggunakan media video tutorial dalam pembelajaran matematika pada materi pokok bangun ruang di kelas VIII di MTSN Binjai (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The use of varied learning media is needed to make it easier for students to understand mathematics. Unfortunately the teacher is still not able to maximize the role of the media in learning mathematics, causing low student learning outcomes. One effort that can be made to improve student mathematics learning outcomes is to apply video tutorial media. The purpose of this study was to determine the results of learning mathematics and student learning activities in the subject matter of Building a Room in class VIII even semester of the Binjai City State Madrasah Tsanawiyah academic year 2017/2018 through the application of video tutorial media. This research is a Classroom Action Research (CAR), with four stages that must be carried out, starting from planning, acting, observing and ending at the reflecting stage. The population used in this study were all students of class VIII MTsN Binjai even semester T.P 2017/2018, totaling 7 classes. The sample selection was carried out by cluster random sampling so that the sample selected was all students of class VIII-1 MTsN Binjai with 38 students. The data collection of this research uses a learning outcome test instrument with multiple choice forms of 25 questions and observation sheets to assess student learning activities during the learning process. From the results of the pretest, it was obtained that the students' mathematics learning outcomes had an average of 45.79 which was still far below the completeness value. After the application of video tutorial instructional media, the learning outcomes have increased with an average post-test learning outcomes being 77.05. The results of observations of student learning activities in cycle 1 obtained an average of 83.66 with the active value category. Based on the research results obtained, it can be concluded that learning with video tutorial media can improve student mathematics learning outcomes and student activeness in learning on the subject matter of Building a Room in class VIII even semeseter MTsN Binjai T.P 2017/2018. Through this research, the researcher hopes that teachers who want to implement learning with this media must pay attention to the allocation of time in designing the lesson plan and pay attention to the points of learning material that will be delivered in the video so that it can be included in the material that must be mastered by students.
Keywords: increase in student learning outcomes; media video tutorials